Social Issues of Modern Cambodia in the 21st Century. The Problem of Violating Children’s Rights - Chorąży, Przemysław (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
The article contains the most important information about the population of Cambodia, its history from ancient times to the present day, the political situation including freedom of expression, the economic situation and the issue of violations of children’s rights. The main objective of this article is to provide the reader with basic information about Cambodia and to analyse the main problems of this Asian country in the second decade of the 21st century, with a special focus on the violation of children’s rights. The aim of the analysis is to answer the question: how does the political-economic situation and the history of the country affect the situation of children in Cambodia. The main part of the article deals with social problems such as poverty, lack of freedom of expression, persecution of political opponents by the authorities, prostitution and human trafficking, including violations of the rights of the youngest and the stigmatisation of orphanage residents.